Making Performance Budgeting Reform Work : A Case Study of Korea - Park, Nowook (World Bank, Washington, DC, 2013)
Performance budgeting is considered one of the essential elements of public financial management reform and has been adopted in many countries. However, it continues to present a significant challenge within the budget process. This case study draws from change management theories to tell the inside story of performance budgeting reform in the Republic of Korea, including the background of the reform, the formation of the reform team, and how the team overcame resistance among stakeholders to implement and institutionalize the performance budgeting system. Policy implications include the importance of (1) strong support from top decision makers and (2) customization of the performance budgeting system to accommodate a country's cultural and socio-economic characteristics. The Korean case also demonstrates that stable, sustainable performance budgeting reform requires capacity building of relevant stakeholders and, sometimes, significant restructuring of organizations to accommodate the new systems.